Hydrological behaviour of an unregulated eastern slope river under changing historical climate. Issue 2 (3rd July 2022) - Zhou, Yixuan; Vidrio-Sahagún, Cuauhtémoc Tonatiuh; Ryan, M. Cathryn; He, Jianxun
Abstract: The Elbow River is an eastern slope river with headwaters in the Rocky Mountains in Alberta whose major end-use is a critical source of municipal water for Calgary. Overwinter precipitation in its watershed falls primarily as snow and accumulates as snowpack until spring melt. Precipitation falls mainly as rain from May until October. The river is unregulated above Calgary's water supply reservoir, and its relatively undeveloped watershed makes it ideal for examining potential climate change impacts on river hydrology. Available historical hydrometeorological data (1967 to 2015) from the basin were assessed to study its hydrological behaviour under a changing climate. The analysis showed significant upward trends in both flow and precipitation variables, especially from 1979 to 2015. Significant increases in both annual flow volume and annual maximum daily flow (AM-flow), and later seasonal occurrence of AM-flow, were not observed in other eastern slope rivers. Although these changes could attenuate predicted water supply shortages, they could also potentially increase flood magnitudes. The analysis also revealed that three sub-watersheds, which are approximately equal in geographic area, contributed differing flow volumes during the high-flow season (May to October). The upper watershed contributed most (∼68%), followed by the middle (∼26%) and lower (∼6%) watersheds, on average. Extreme high-flow events (ie >90 th percentile AM-flow) were strongly related to high rainfall events, but not significantly related to snowpack loss (or melt). Moderate AM-flows were positively related to both the cumulative snowpack loss before the high-flow season and the cumulative antecedent precipitation prior to the AM-flow, suggesting that the antecedent soil moisture conditions could play a role. Predictions of climate change impacts on this eastern slope river's hydrology should thus consider the effects of meteorological variables and the moisture conditions of the watershed.